A)3(2y+5x)-2(3y-2x-1)+18=
B)-2(x-y+2)+3(2x+2y-7)=
C)½(6-2x-4y)+8(x-½y+4)=
D)1½(4+6x-2y)+4(-x-y-1)=
E)5x-2y+3x-6)+4y-(2x+y)=
F)-3x-2y+(8x-1½y+5)-½(x-y)=
G)8(4y-2x+3)-½(x+y)+6=
H)¾(x-y+4)-2(x-¼y+5)=
I)0,2(x-2y+5)-0,4(x-y+7)=
J)0,7(2x-0,25y+8)-0,12(x-y+5)

2

Odpowiedzi

2010-02-28T13:17:48+01:00
A)3(2y+5x)-2(3y-2x-1)+18= 6y+15x-6y+4x+2= 19x+2

B)-2(x-y+2)+3(2x+2y-7)= -2x+2y-4+6x+6y-21= 4x+8y-25

C)½(6-2x-4y)+8(x-½y+4)=3-x-2y+8x-4y+32= 7x-6y+35

D)1½(4+6x-2y)+4(-x-y-1)= 6+9x-3y-4x-4y-4=2+5x-7y

E)5x-2y+3x-6)+4y-(2x+y)=? brakuje chyba lewej strony nawiasu gdzies, 5x-2y+3x-6+4y-2x-y= 6x+y-6

F)-3x-2y+(8x-1½y+5)-½(x-y)=-3x-2y+8x-1,5y+5-0,5x+0,5y= 4,5x-3y+5

G)8(4y-2x+3)-½(x+y)+6=32y-16x+24-0,5x-0,5y= -16,5x+31,5y+24

H)¾(x-y+4)-2(x-¼y+5)= 0,75x-0,75y+3-2x+0,5y-10=-1,25x-0,25y-7

I)0,2(x-2y+5)-0,4(x-y+7)=0,2x-0,4y+1-0,4x+0,4y-2,8= -0,2x-1,8

J)0,7(2x-0,25y+8)-0,12(x-y+5) = 1,4x-0,175y+5,6-0,12x+0,12y-0,6= 1,28x-0,055y+5
2010-02-28T13:30:03+01:00
A) 3(2y+5x)-2(3y-2x-1)+18=6y+15x-6y+4x+2=19x+2

B) -2(x-y+2)+3(2x+2y-7)= -2x + 2y - 4 + 6x + 6y - 21= 4x + 8y - 25

C) ½(6-2x-4y)+8(x-½y+4)= 3 - 1x - 2y + 8x - 4y + 32 = 7x - 6y + 35

D) 1½(4+6x-2y)+4(-x-y-1)= 6 + 9x - 3y - 4x - 4y - 4 = -5x - 7y +2

E) (5x-2y+3x-6)+4y-(2x+y)= 5x - 2y +3x - 6 + 4y - 2x - y = 6x + 1y-6

F) -3x-2y+(8x-1½y+5)-½(x-y)=-3x-2y+8x-1½y+5-½x+½y=4½x-3y+5

G) 8(4y-2x+3)-½(x+y)+6=32y-16x+24-½x-½y+6=-16½x+31½y+30

H) ¾(x-y+4)-2(x-¼y+5)=¾x-¾y+3-2x+½y-10=-1¼x-¼y+7

I) 0,2(x-2y+5)-0,4(x-y+7)=0,2x-0,4y+1-0,4x+0,4y-2,8=-0,2x-1,8

J) 0,7(2x-0,25y+8)-0,12(x-y+5)=1,4x-0,175y+5,6-0,12x+0,12y-0,6= 1,28x-0,055y+5